Sistem Transaksi Murabahah Bil ‘Urbuun dan Pertanggungjawaban Risiko terhadap Redistribusi Tanah Land Reform Ditinjau Etika Bisnis Islam - Idhar Idhar (ISLAMINOMICS: JOURNAL OF ISLAMIC ECONOMICS, BUSINESS AND FINANCE, 2023)
The emergence of the Murabahah bil 'Urbuun transaction system in land reform land redistribution can be attributed to the accommodation provided for the transaction process in Ministerial Regulation No. 224 of 1961, which pertains to the implementation of land distribution and compensation provisions, and the issuance of DSN MUI Fatwa No. 04/DSN-MUI/IV/2000 on murabahah. The Murabahah bil 'Urbuun system comprises the first two components of Al Bai Al Muajjal, involving the sale and purchase of payments made in a deferred manner, and Al Bai Bi At-Taqsith, which encompasses buying and selling with payments made in installments or gradually. This arrangement has resulted in the accumulation and concentration of land ownership among a group of urban residents, including traders, private employees, and civil servants, leading to excessive land ownership redistribution. Motivated by this background, this study seeks to examine the Murabahah bil 'Urbuun transaction system and the risk accountability associated with land reform land redistribution from the perspective of Islamic economic ethics. The research adopts a juridical empirical approach using descriptive analysis and employs field study methods, including interviews and observations, with a deductive data analysis approach. The study's findings indicate that the Murabahah bil 'Urbuun transaction system and the risk accountability in land reform land redistribution are grounded in Islamic normative foundations such as unity, justice, freedom, and responsibility, guided by the five principles of muamalah, namely: la yakun dawlatan bayn al-agniya (avoiding concentration of wealth), 'antaradine (interdependence), tabadul al-manafi' (exchange of benefits), takaful al-ijtima' (social solidarity), and haq al-lah wa hal al-adami (balance between divine rights and human rights). This research contributes to a better understanding of the Murabahah bil 'Urbuun transaction system's implications in the context of land reform land redistribution and provides insights into the risk accountability aspects from the perspective of Islamic economic ethics. By shedding light on the ethical considerations in such transactions, this study may aid policymakers and stakeholders in formulating more equitable and responsible land redistribution strategies in line with Islamic principles.